"I have my own rules, too" female adolescents' exploration of sexuality and development of sexual identity in watching pornography. - Pontica, Mae Jane B. (May Jane B. Pontica, 2018)
The purpose of this study is to understand how female adolescents explore their sexual identity through watching pornography. Sexuality is a complex dynamic in the society which is essential to all humans. However, not everyone has the privilege to explore their sexuality. The existence of sexual double standard in our society suppresses the exploration of sexuality of females but tends to be more lenient among males. Recent studies have shown that pornography is one avenue for adolescents to explore their sexual double standards and lack of information on female sexuality, female adolescents resort to pornography as a material to learn about their sexual identity. A qualitative research method was employed in this study, based on focused interviews of six female adolescents who actively watch porn videos. Their transcripts provided codes which resulted in four major themes through the use of Josselson's identity development theory of women. The results of the study are: drifting path to pornography, purveyors of female sexuality, exploration of female sexuality, and understanding female sexuality. The data from the study provides practical implications which aid female adolescents in exploring their sexual identity and mitigate sexual double standards in the society.